Effect of Urinary Retention on the Satisfaction and Complication Rate in Benign Prostatic Hyperplasia Patients Undergoing Prostatectomy - Mai A. Banakhar, (Journal of King Abdulaziz University: Medical Sciences, 2023)
A cohort study from January 2000 till January 2005 included all patients who underwent prostatic surgery with histopathology report of benign prostatic hyperplasia. Patients were divided into elective or retention group. Data of patient demographics, satisfaction and postoperative complications were collected. Total of 119 patients, retention (n = 30), elective group (n = 89). Retention rate was 25%. There was no eff ect of retention on postoperative complication (elective = 44%, retention = 41%) p value = 0.826, odds ratio 0.878, CI (0.363 - 2.124) nor any eff ect on patients' satisfaction (elective = 54%, retention = 59%) p value = 0.661, odds ration = 1.256, CI (0.520 - 3.034). Patients’ age and prostate size did not show any effect on postoperative outcome. While presence of infl ammatory cells in benign prostatic hyperplasia (BPH) histopathology showed positive eff ect on satisfaction (BPH alone = 47%, BPH + infl ammation = 71%) p value = 0.037, and a protective eff ect on postoperative complications (BPH alone = 45%, +BPH with infl ammation = 18%) p value = 0.167. Conclusion: Retention rate is comparable to the international reports. The presence of infl ammatory cells in the benign prostatic hyperplasia histopathology showed a positive eff ect on postoperative satisfaction.